On the Performance of the Current MANET Routing Protocols for VoIP, HTTP, and FTP Applications - Waheb A. Jabbar; Mahamod Ismail; Rosdiadee Nordin (Journal of Computer Networks and Communications)
The recent advances of ensemble mobile environment of smart devices with embedded sensors have enabled the MANET to play a key role in the smart cities as well as WSN and WMN. However, these smart devices are still limited in terms of energy, processor, and memory. Moreover, the efficient routing for reliable network connectivity at anytime, anywhere, and about everything is still a challenge in multihop wireless networks. This paper evaluates the QoS and energy efficiency of three active routing protocols: (i) OLSRv2, a successor to OLSR, (ii) DYMO, a successor to both DSR and AODV, and (iii) MP-OLSR multipath extension to OLSRv2. In contrast to the related previous works which focused only on CBR traffic without considering the influence of specific traffic types on the performance of routing protocols, this work focused on this area from a different perspective. It evaluates the performance of three internet-based traffic types that can be used in the smart city applications: VoIP, HTTP, and FTP using different simulation models. The impact of the network density, load traffic, and nodes mobility on the considered protocols was evaluated by considering particular performance metrics for each traffic application. Based on the results, the study concludes by presenting useful recommendations for future work.